Utilization of Tomi-Tomi Juice (Flacourtia inermis Roxb) as a Flavoring Agent in The Production of Coconut Isotonic Drink - Sophia Grace Sipahelut; Centhya Victorin Maitimu; Sri Rejeki; John Alfred Patty (Universitas Sebelas Maret (UNS), 2024)
This study aims to study the chemical and organoleptic characteristics of an isotonic drink of aged coconut water with the addition of tomi-tomi fruit juice as a flavoring agent. This study was designed using a single factor Completely Randomized Design (CRD) with 4 treatment levels, ratios of old coconut water and tomi-tomi fruit juice, namely 90%:10%, 80%:20%, 70%:30%, and 60%:40 %. Parameters analyzed included: total phenol, total dissolved solids, pH and organoleptic tests including hedonic and hedonic quality tests (taste, aroma, color, turbidity, overall acceptability). The results showed that the higher the ratio of tomi-tomi juice added, the total phenol of isotonic coconut water drink increased, but the total dissolved solids and pH decreased. The use of tomi-tomi fruit juice 80%:20% is the best flavoring agent because it produces an isotonic drink flavor that is preferred by panelists compared to other treatments, with a total phenol content of 2.92 mg gallic acid/100 mL, total dissolved solids of 16.03° Brix, and a pH of 4.21.